(untitled) (Research, Society and Development, 2021)
Nitrous oxide (N2O) is one of the main gases that contributes to the greenhouse effect. With a Global Warming Potential (GWP) 265 times greater than that of carbon dioxide (CO2), over a 100-year horizon, N2O also has the potential for the depreciation of the ozone layer. The activities related to agriculture and livestock are responsible for approximately 60% of the global anthropogenic emissions of this gas to the atmosphere. In Brazil, the sector corresponds to 37% of total emissions. The objectives of this review article were: (i) To verify which are the main processes involved in N2O emissions in soils fertilized with swine manure; (ii) What are the direct emissions on these soils under different management systems, and; (iii) What are the possible strategies for controlling and mitigating N2O emissions. Therefore, an exploratory and qualitative research of articles was carried out using the following keywords: óxido nitroso’, ‘nitrous oxide’, ‘N2O’, ‘nitrogênio’, ‘nitrogen’, ‘suínos, ‘pig, ‘swine’, ‘dejetos’, ‘manure’ and ‘slurry’. Effects of pig diet, manure treatment systems, presence of heavy metals in the soil and moisture content of manure on N2O emissions were verified. Therefore, we recommend integrated studies of the quantitative and qualitative impacts of the levels and sources of nitrogen in the animals’ diets on N2O emissions after the application of these wastes to the soil. We also recommend studies related to the effects of copper and zinc contents added to the soil via swine manure on enzymes that catalyze the biotic denitrification process in the soil.